Comprehensive Musicianship, A Practical Resource - Harlow, Randall; Peyton, Heather; Schwabe, Jonathan Clarke; Swilley, Daniel (Open textbook library., 2023)
This OER presents an integrated suite of learning resources developed for the core music theory and musicianship curriculum at the University of Northern Iowa School of Music. It provides a more comprehensive symbiosis of musicianship and music theory learning than can be found in existing textbooks, including engaging and progressive video demonstrations and interactive listening and vocal exercises that integrate musical knowledge with foundational musical skills.